Metabolites Identification of Chemical Constituents From the Eggplant (Solanum melongena L.) Calyx in Rats by UPLC/ESI/qTOF-MS Analysis and Their Cytotoxic Activities - Song, Yuanyuan; Mei, Ting; Liu, Yan; Kong, Shengnan; Zhang, Jincheng; Xie, Minzhen; Ou, Shan; Liang, Meixia; Wang, Qi (Frontiers in Pharmacology, 2021)
Eggplant (Solanum melongena L.) Calyx is a medicinal and edible traditional Chinese medicine with anti-inflammatory, anti-oxidant, and anti-cancer properties. However, the pharmacodynamic components and metabolic characteristics remain unclear. Amide and phenylpropanoid were the two main constituents, and four amides, including n-trans-p-coumaroyltyramine (1), n-trans-p-coumaroyloctopamine (2), n-trans-p-coumaroylnoradrenline (3), n-trans-feruloyloctopamine (4), and a phenylpropanoid neochlorogenic acid (5) were selected. In this study, these five representative compounds showed cytotoxic activities on A549, HCT116, and MCF7 cells. In addition, the metabolites of 1–5 from the eggplant calyx in rats were identified. In total, 23, 37, 29, and 17 metabolites were separately characterized in rat plasma, urine, feces, and livers, by UPLC/ESI/qTOF-MS analysis. The metabolism of amides and phenylpropanoid was mainly involved in hydroxylation, methylation, glucuronidation, or sulfation reactions. Two hydroxylated metabolites (1-M2 and 2-M3) were clearly identified by comparison with reference standards. Rat liver microsome incubation experiments indicated that P450 enzymes could hydroxylate 1–5, and the methylation reaction of the 7-hydroxyl was also observed. This is the first study on the in vivo metabolism of these compounds, which lays a foundation for follow-up studies on pharmacodynamic evaluations and mechanisms.